2012
DOI: 10.1179/2046905512y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of ABO haemolytic disease in the newborn

Abstract: ABO incompatibility was observed in 17.3% of pregnancies with almost equal O-A and O-B frequency. About a third of infants had significant hyperbilirubinaemia. There was no difference in severity between those with O-A and O-B HDN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
31
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 21 publications
8
31
0
10
Order By: Relevance
“…Our study results did not show any differences when comparing the outcomes for infants with blood group A to those with blood group B. These results correlate with a previous report …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study results did not show any differences when comparing the outcomes for infants with blood group A to those with blood group B. These results correlate with a previous report …”
Section: Discussionsupporting
confidence: 91%
“…[17,18] A previous study among term infants with ABO incompatibility showed that about one-third had severe hyperbilirubinemia requiring phototherapy. [16] As expected in preterm infants, this study showed higher rates of hyperbilirubinemia requiring phototherapy (ß50%) among all preterm cohorts including controls, and even higher rates (ß85%) among the lower GA subgroup (<32 weeks GA) and their controls. Nevertheless, differences between the infants with ABO incompatibility and the controls were found only among the more mature infants of 32-34 weeks GA.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations